Identification and Characterization of Erysiphe necator-Responsive MicroRNAs in Chinese Wild Vitis pseudoreticulata by High-Throughput Sequencing - Han, Lijuan; Weng, Kai; Ma, Hui; Xiang, Gaoqing; Li, Zhiqian; Wang, Yuejin; Liu, Guotian; Xu, Yan (Frontiers in Plant Science, 2016)
Grapevine powdery mildew is one of the most damaging fungal diseases. Therefore a precise understanding of the grapevine disease resistance system becomes a subject of significant importance. Plant microRNAs(miRNAs) have been implicated to play regulatory roles in plant biotic stress responses. In this study, high-throughput sequencing and miRDeep-P were employed to identify miRNAs in Chinese wild Vitis pseudoreticulata leaves under Erysiphe necator inoculation. Altogether, 126 previously identified microRNAs and 124 novel candidates of miRNA genes were detected. Among them, 43 conserved miRNAs belong to 20 families and 23 non-conserved but previously-known miRNAs belong to 15 families. Under E. necator inoculation condition, there were 119 and 131 miRNAs respectively down and up-regulated, and the expression changes of 32 miRNAs were significant. Furthermore, the expression patterns of some miRNAs were validated by semi-quantitative RT-PCR and qRT-PCR. A total of 485 target genes were predicted and categorized by Gene Ontology (GO). In addition, we screened 14 vvi-miRNAs with 36 targets which might be involved in grape powdery mildew resistance. We also detected highly accumulated vvi-NewmiR2118 from accession ‘Baihe-35-1’, whose targets were mostly NBS-LRR resistance genes. It was down-regulated rapidly and strongly in ‘Baihe-35-1’ leaves after inoculated with E. necator, indicating its involvement in grape powdery mildew resistance. Using histochemical staining and GUS fluorescence quantitative assay, we verified the interaction of vvi-NewmiR2118 with RPP13.